Is a firm a firm? A Stackelberg experiment - Andreas Hildenbrand (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
Industrial organization is mainly concerned with the behavior of large firms. Experimental industrial organization therefore faces a problem: How can firms be brought into the laboratory? The main approach relies on framing: Call individuals firms! This experimental approach is not in line with modern industrial organization, according to which a firm's market behavior is also determined by its organizational structure. In this paper, a Stackelberg experiment is considered in order to answer the question whether framing individual decision making as organizational decision making or implementing an organizational structure is more effective in generating profit-maximizing behavior. Firms are either represented by individuals or by teams. I find that teams' quantity choices are more in line with the assumption of profit maximization than individuals' choices. Compared to individuals, teams appear to be less inequality averse.
Keywords: C72; C91; C92; D43; L130; 330; industrial organization; Stackelberg game; individual behavior; team behavior; framing; experimental economics; Industrieökonomik; Test; Unternehmenspolitik; Framing; Arbeitsgruppe